2012
DOI: 10.2147/ijn.s24711
|View full text |Cite
|
Sign up to set email alerts
|

Combination of TRAIL and actinomycin D liposomes enhances antitumor effect in non-small cell lung cancer

Abstract: Abstract:The intractability of non-small cell lung cancer (NSCLC) to multimodality treatments plays a large part in its extremely poor prognosis. Tumor necrosis factor-related apoptosisinducing ligand (TRAIL) is a promising cytokine for selective induction of apoptosis in cancer cells; however, many NSCLC cell lines are resistant to TRAIL-induced apoptosis. The therapeutic effect can be restored by treatments combining TRAIL with chemotherapeutic agents. Actinomycin D (ActD) can sensitize NSCLC cells to TRAIL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…To engineer the NP-core, different chemical compositions have been used such as human serum albumin, 153 , 167 , 168 poly (lactic-co-glycolic) acid (PLGA) microspheres, 151 , 152 , 169 a combination of PEGylated heparin and poly- l -lysine, 154 magnetic ferric oxide 170 or liposomes. 67 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 Among them, thanks to their versatility, liposomes have emerged as the most versatile of these platforms. Moreover, liposomes can be easily modified size- and composition-wise depending on the desired physicochemical properties.…”
Section: Targeting Trail To Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…To engineer the NP-core, different chemical compositions have been used such as human serum albumin, 153 , 167 , 168 poly (lactic-co-glycolic) acid (PLGA) microspheres, 151 , 152 , 169 a combination of PEGylated heparin and poly- l -lysine, 154 magnetic ferric oxide 170 or liposomes. 67 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 Among them, thanks to their versatility, liposomes have emerged as the most versatile of these platforms. Moreover, liposomes can be easily modified size- and composition-wise depending on the desired physicochemical properties.…”
Section: Targeting Trail To Cancer Cellsmentioning
confidence: 99%
“…Concerning the manner in which TRAIL is integrated with the NPs, there are two different strategies: (i) to encapsulate TRAIL inside the particles so that they are released from the particle in a constant and stable manner; 151 , 152 , 153 , 154 , 169 , 173 , 174 , 175 , 176 or (ii) to attach TRAIL to the surface of the nanoparticles so that TRAIL gets immobilized, resembling the physiological membrane-bound protein, increasing its bioactivity. 168 , 170 , 171 , 172 , 177 , 178 , 179 …”
Section: Targeting Trail To Cancer Cellsmentioning
confidence: 99%
“…Although A549 lung cancer cells are resistant to TRAIL treatment, they become sensitized when TRAIL is combined with other agents [32]. In the present study, we examined the effects of GlcNAc in combination with TRAIL.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have shown that many types of cancers, including some NSCLCs, are resistant to the apoptotic effects of TRAIL [32, 37-39]. It has been reported that absence of DR expression and clustering may be a major cause of resistance to TRAIL-based cancer therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…The death receptor apoptotic pathway has previously been proposed as an anti-cancer drug target in human lung cancer [39,40]. Traditional Chinese medicine (TCM) that could stimulate the death receptor apoptotic pathway should have therapeutic potential in human lung cancer treatment [41-43].…”
Section: Discussionmentioning
confidence: 99%